No Signs of Inflammation during Knee Surgery with Ischemia: A Study Involving Inhaled Nitric Oxide - Hållström, Lars; Frostell, Claes; Herrlin, Anders; Lindroos, Eva; Lundberg, Ingrid; Soop, Anne (Mediators of Inflammation, 2014)
Nitric oxide donors and inhaled nitric oxide (iNO) may decrease ischemia/reperfusion injury as reported in animal and human models. We investigated whether the attenuation of reperfusion injury, seen by others, in patients undergoing knee arthroplasty could be reproduced when patients had spinal anesthesia. 45 consecutive patients were randomized into three groups (n=15). Groups 1 and 3 were receiving iNO 80 ppm or placebo (nitrogen, N2) throughout the entire operation, and group 2 only received iNO in the beginning and at the end of the operation. Blood samples were collected before surgery, at the end of the surgery, and 2 hours postoperatively. Muscle biopsies were taken from quadriceps femoris muscle before and after ischemia. There were no increases in plasma levels of soluble adhesion molecules: ICAM, VCAM, P-selectin, E-selectin, or of HMGB1, in any of the groups. There were low numbers of CD68+ macrophages and of endothelial cells expression of ICAM, VCAM, and P-selectin in the muscle analyzed by immunohistochemistry, prior to and after ischemia. No signs of endothelial cell activation or inflammatory response neither systemically nor locally could be detected. The absence of inflammatory response questions this model of ischemia/reperfusion, but may also be related to the choice of anesthetic method EudraCTnr.